Effectiveness of Tong-Xie-Yao-Fang combined with Si-Ni-San for irritable bowel syndrome: A protocol for systematic review and meta-analysis. Issue 11 (19th March 2021) - Jiang, Jiawang; Chen, Yun; Hu, Ziyi; Li, Huaiyu; Ye, Jing; Yu, Zhiying; Tang, Haiyi
Abstract: Background: Irritable bowel syndrome (IBS) has a high morbidity rate worldwide, but there are no effective treatment measures, which seriously affect people's lives. Previous clinical studies on Tong-Xie-Yao-Fang (TXYF) combined with Si-Ni-San (SNS) in the treatment of IBS have been increasing, but there is no systematic evaluation. This study aims to systematically study the effectiveness of TXYF combined with SNS in the treatment of IBS. Methods: The PubMed, EMBASE, Science Network, Cochrane Library, Chinese Biomedical Literature, Wanfang Chinese Digital Journal and Conference Database, China National Knowledge Infrastructure Database and VIP China Science and Technology Journal Database (VIP) will be used Search related literature, and the search time is from the date of establishment to February 2021. The National Institutes of Health clinical registry Clinical Trials, International Clinical Trials Registry Platform and the Chinese clinical trial registration platform will be searched to find ongoing or unpublished trials. After screening the literature according to the criteria, two researchers independently extracted data according to a predetermined table. The primary outcome is total effective rate. The RevMan 5.3.5 software will be used for statistical analysis. Finally, the recommendation, evaluation, development and evaluation system will be used to evaluate the quality evidence for each result. Results: This study will provide the latest evidence of efficacy for the TXYF combined with SNS for IBS. Conclusion: The effectiveness of TXYF combined with SNS for IBS will be evaluated. Unique INPLASY number: INPLASY202120075.